Two-phase metal gel and preparation method thereof
By preparing a two-phase metal gel, a continuous phase is formed in a polyvinyl alcohol polymer network using rigid metal particles and flexible liquid metal. This solves the problem of achieving both high conductivity and high toughness in flexible materials, and achieves a balance between the two, making it suitable for flexible electronic products.
Patent Information
- Application Number
- CN202411703967.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Existing flexible materials cannot simultaneously achieve high conductivity and high toughness, thus failing to meet the requirements of flexible electronic products.
By preparing a two-phase metal gel, a continuous phase is formed in the polyvinyl alcohol polymer network by rigid metal particles and flexible liquid metal, establishing a good interface and stress transfer mechanism, thereby achieving high conductivity and high toughness.
It achieves a balance between high conductivity and high toughness, and the material exhibits excellent electronic conductivity and toughness, making it suitable for flexible electronic products.
Smart Images

Figure CN119446628A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gel and polymer composite materials, and more specifically, to a two-phase metal gel and a preparation method thereof, and application of the metal gel in flexible electronic products. Background Art
[0002] The development of flexible electronic products requires flexible materials to achieve both high conductivity and high toughness. 6 Metal conductivity above S / m can reduce the internal resistance of the device, thereby improving the signal transmission quality and minimizing energy consumption. At the same time, high toughness can ensure the stability of the device structure, making it resistant to the inevitable damage suffered during use, such as stretching, tearing or puncture, and can reduce resource waste and environmental pollution, which is conducive to the sustainable development of electronic products.
[0003] However, the materials currently developed cannot achieve high conductivity, high toughness and flexibility. Among them, the conductivity of metal conductors exceeds (10 6 S / m), but its inherent rigidity makes it unsuitable for flexible electronics. In addition, materials based on conductive polymers, such as polyaniline and polypyrrole, have low conductivity (10 -1 -10 4 S / m), and usually shows less than 5MJ / m 3 The toughness of the composite material is not good enough to meet the needs. In order to solve these limitations, the composite material developed by adding conductive fillers to the polymer matrix is expected to have both high conductivity and high toughness. However, although adding a small amount of conductive fillers can improve toughness, the conductivity of such composite materials is not ideal due to the lack of continuous conductive paths (10 1 -10 5 S / m). Increasing the content of conductive fillers can significantly improve the conductivity, but a high content of rigid fillers will cause more defects to form inside the material, making it brittle as a whole. On the contrary, in the relevant research of our laboratory (Adv.Mater.2024,2409137.Doi:10.1002 / adma.202409137), it was found that adding more flexible fillers, such as liquid metal, can improve the electrical properties of the material, but at the same time it will also reduce the mechanical strength of the material, resulting in lower toughness (<3MJ / m 3 ). Therefore, there are still great challenges in developing flexible materials that have both metallic-level conductivity and high toughness. Summary of the invention
[0004] 1. Technical issues to be solved
[0005] In view of the problem that flexible materials in the prior art cannot have both metal-grade electronic conductivity and high toughness, the present invention hopes to develop a new type of material based on the relevant research of this laboratory, so that it has both metal-grade electronic conductivity and high toughness to meet the requirements of flexible electronic products for conductivity and toughness.
[0006] 2. Technical solution
[0007] Based on the above purpose, the present invention provides a two-phase metal gel material, which forms a continuous phase inside the material and is fixed by a three-dimensional continuous polymer network to achieve metal-level conductivity. In addition, due to the good interface between the two-phase metals and between the two-phase metals and the polymers in the material, effective stress transfer is achieved inside the gel, so that it has three stress dissipation modes and achieves high toughness. Specifically, the purpose of the present invention is achieved through the following technical solutions:
[0008] [Method for preparing two-phase metal gel and two-phase metal gel prepared therefrom]
[0009] The first aspect of the present invention provides a method for preparing a two-phase metal gel, comprising the steps of:
[0010] Preparation of dual-phase metal: rigid metal particles and flexible liquid metal are mixed in an acidic solution or an alkaline solution, and separated after continuous stirring to obtain dual-phase metal;
[0011] Preparing a polyvinyl alcohol solution: dissolving polyvinyl alcohol particles in a good solvent to obtain a polyvinyl alcohol solution;
[0012] Preparing a two-phase metal-polyvinyl alcohol mixed solution: mixing and dispersing the two-phase metal with the polyvinyl alcohol solution to obtain a two-phase metal-polyvinyl alcohol mixed solution;
[0013] Drying: drying the two-phase metal-polyvinyl alcohol mixed solution to obtain a two-phase metal gel.
[0014] The present invention forms a two-phase metal with rigid metal particles and flexible liquid metal, which are dispersed in a continuous polyvinyl alcohol polymer network. The rigid metal particles provide toughness for the two-phase metal gel. The metal wetting interaction between the rigid metal particles and the flexible liquid metal, and the hydrogen bonding between the flexible liquid metal and the polyvinyl alcohol network, establish a good interface and promote stress transfer between the components. Therefore, when the material is deformed, the applied force causes the deformation of the polymer network, and energy dissipation occurs; at the same time, the flexible liquid metal and the polymer network deform synchronously, which contributes to additional energy dissipation, and the rigid metal particles, as stress concentration points, also absorb part of the applied energy. Moreover, the two-phase metal formed by the rigid metal particles and the flexible liquid metal can overcome the problem of low electronic conductivity of the metal gel formed by the liquid metal and the polyvinyl alcohol.
[0015] As a preferred step of preparing the dual-phase metal of the present invention, the rigid metal particles are selected from one or more of iron, nickel, copper, silver, gold or neodymium iron boron alloy; the selection of metal particles needs to meet the requirements of both rigidity and high conductivity, so non-conductive metals such as aluminum cannot be selected as rigid metal particles to form a dual-phase metal with the flexible liquid metal;
[0016] Further preferably, the rigid metal particles are copper, and the copper powder and the liquid metal can form an intermetallic compound CuGa2, and the toughness of the finally obtained copper-two-phase metal gel is significantly higher than the toughness of other rigid metal particle two-phase metal gels;
[0017] Further preferably, the particle size of the rigid metal is 50nm to 10μm. For example, the data in the preparation example show that the two-phase metal gel prepared from copper powder with a particle size range of 50nm to 10μm has good electronic conductivity and toughness;
[0018] Preferably, the flexible liquid metal is selected from one or two of gallium-indium alloy and gallium-indium-tin alloy; although mercury, cesium, francium and the like are also liquid metals, their applications are greatly limited due to their toxicity, radioactivity or danger. Gallium, indium, tin metals and their alloys are the most commonly studied and applied liquid metal materials because of their safety, non-toxicity and excellent performance.
[0019] Further preferably, the mass fraction of Ga in the gallium-indium alloy is 75.50% wt and In 24.50% wt ; The mass fraction of Ga in the gallium-indium-tin alloy is 68.50% wt ,、In 21.50% wt and Sn 10.00% wt ;
[0020] Preferably, the weight ratio of the rigid metal particles to the flexible liquid metal is between 1:6 and 1:20, preferably 1:12; this can ensure that the rigid metal particles are completely immersed in the flexible liquid metal and that the rigid metal particles effectively improve the conductivity of the two-phase metal in the polymer network.
[0021] Preferably, the prepared two-phase metal is one or more of an iron-gallium-indium alloy two-phase metal, a nickel-gallium-indium alloy two-phase metal, a copper-gallium-indium alloy two-phase metal, a silver-gallium-indium alloy two-phase metal, a gold-gallium-indium alloy two-phase metal, a neodymium-iron-boron alloy-gallium-indium alloy two-phase metal, an iron-gallium-indium-tin alloy two-phase metal, a nickel-gallium-indium-tin alloy two-phase metal, a copper-gallium-indium-tin alloy two-phase metal, a silver-gallium-indium-tin alloy two-phase metal, a gold-gallium-indium-tin alloy two-phase metal or a neodymium-iron-boron alloy-gallium-indium-tin alloy two-phase metal;
[0022] The data in the examples show that the electronic conductivity of the two-phase metal gel material prepared by using the above two-phase metal is greater than or equal to 2.00×10 6 S / m, toughness is greater than or equal to 7MJ·m 3 , the values of Young’s modulus are all less than or equal to 7MPa, achieving a balance between high electronic conductivity, high toughness and flexibility.
[0023] Preferably, the concentration of the acidic solution or alkaline solution is 1 to 4 M; further preferably, the volume ratio of the dual-phase metal to the acidic solution or alkaline solution is less than 1:5, preferably less than 1:10;
[0024] The acidic solution or alkaline solution mainly provides conditions for uniform mixing of rigid metal particles and flexible liquid metal.
[0025] Preferably, the rigid metal particles and the flexible liquid metal are mixed in an acidic solution or an alkaline solution, and stirred continuously for 0.5 to 1 hour at a stirring speed of 8000 rpm to 15000 rpm;
[0026] Rigid metal particles can be completely infiltrated and evenly dispersed in the flexible liquid metal, making the two-phase metal homogeneous, ensuring the uniformity of the electrical conductivity of the two-phase metal and stable electromechanical coupling performance; at the same time, the strength and compatibility of the conductive filler are improved to form a stable interface with the polyvinyl alcohol polymer network.
[0027] As a preferred step of preparing the polyvinyl alcohol solution of the present invention, 8 wt% to 12 wt% of polyvinyl alcohol particles are dissolved in a good solvent, and magnetic stirring is continuously performed at a temperature above 95° C. for 1 hour until dissolved;
[0028] Further preferably, 10 wt % of polyvinyl alcohol particles are dissolved in a good solvent and continuously stirred with magnetic force at 95° C. for 1 hour until dissolved;
[0029] More preferably, the good solvent is one or both of deionized water and dimethyl sulfoxide (DMSO).
[0030] As a preferred step of preparing a dual-phase metal-polyvinyl alcohol mixed solution of the present invention, the dual-phase metal and the polyvinyl alcohol solution are mixed and dispersed in a weight ratio of 1:1 to 7:3, and most preferably 13:7;
[0031] The above ratio ensures that the two-phase metals are interconnected in the entire material to form a continuous phase, providing a good electron path for the two-phase metal gel; it also ensures that the polyvinyl alcohol polymer network presents a continuous three-dimensional porous structure, providing good mechanical support for the two-phase metal gel;
[0032] More preferably, the mixing and dispersing method is to use a handheld homogenizer to stir and shear at a speed of 8000 rpm to 15000 rpm for 5 min to 15 min.
[0033] After the two-phase metal undergoes high-speed stirring and shearing in the homogenizer, it forms micron droplets dispersed in the solution, with the polymer network partially wrapped around the metal surface and the rest dispersed in the good solvent.
[0034] As a preferred drying step of the present invention, the obtained two-phase metal-polyvinyl alcohol mixed solution is added to a polytetrafluoroethylene watch glass, and placed in an environment of 25° C. to 80° C. to remove the good solvent;
[0035] Further preferably, the obtained two-phase metal-polyvinyl alcohol mixed solution is added into a polytetrafluoroethylene watch glass, and placed in an environment of 60° C. to remove the good solvent;
[0036] As the drying progresses, the polyvinyl alcohol molecules are physically cross-linked to form a three-dimensional network, and the two-phase metal gradually approaches. Finally, after demoulding, the two-phase metal forms a continuous phase, and the three-dimensional continuous polyvinyl alcohol polymer network is in the two-phase metal continuous phase to maintain the stability of the material.
[0037] The second aspect of the present invention provides a two-phase metal gel prepared by the method for preparing a two-phase metal gel according to any embodiment of the first aspect of the present invention.
[0038] As a preferred embodiment of the two-phase metal gel of the second aspect of the present invention, the electronic conductivity of the two-phase metal gel is greater than or equal to 2.00×10 6 S / m, toughness greater than or equal to 7MJ·m 3 , the value of Young’s modulus is less than or equal to 7MPa.
[0039] [Two-phase metal gel]
[0040] The third aspect of the present invention provides a two-phase metal gel, comprising a two-phase metal and polyvinyl alcohol, wherein the two-phase metal is dispersed in the polyvinyl alcohol;
[0041] The two-phase metal comprises rigid metal particles and flexible liquid metal;
[0042] In the two-phase metal, the rigid metal particles have a size of 50 nm to 10 μm;
[0043] In the two-phase metal, the mass ratio of rigid metal particles to flexible liquid metal is 1:(6-20);
[0044] The mass ratio of the two-phase metal to polyvinyl alcohol is (30-70):3.
[0045] The present invention forms a two-phase metal with rigid metal particles and flexible liquid metal, which are dispersed in a continuous polyvinyl alcohol polymer network. The rigid metal particles provide toughness for the two-phase metal gel. The metal wetting interaction between the rigid metal particles and the flexible liquid metal, and the hydrogen bonding between the flexible liquid metal and the polyvinyl alcohol network, establish a good interface and promote stress transfer between the components. Therefore, when the material is deformed, the applied force causes the deformation of the polymer network, and energy dissipation occurs; at the same time, the flexible liquid metal and the polymer network deform synchronously, which contributes to additional energy dissipation, and the rigid metal particles, as stress concentration points, also absorb part of the applied energy. Moreover, the two-phase metal formed by the rigid metal particles and the flexible liquid metal can overcome the problem of low electronic conductivity of the metal gel formed by the liquid metal and the polyvinyl alcohol.
[0046] As a preferred embodiment of the two-phase metal gel of the third aspect of the present invention, the rigid metal particles are selected from one or more of iron, nickel, copper, silver, gold or neodymium iron boron alloy;
[0047] The flexible liquid metal is selected from one or both of gallium-indium alloy and gallium-indium-tin alloy.
[0048] As a preference for the two-phase metal gel of the third aspect of the present invention, the rigid metal particles are copper.
[0049] As a preferred dual-phase metal gel of the third aspect of the present invention, the dual-phase metal is selected from one or more of iron-gallium-indium alloy dual-phase metal, nickel-gallium-indium alloy dual-phase metal, copper-gallium-indium alloy dual-phase metal, silver-gallium-indium alloy dual-phase metal, gold-gallium-indium alloy dual-phase metal, neodymium-iron-boron alloy-gallium-indium alloy dual-phase metal, iron-gallium-indium-tin alloy dual-phase metal, nickel-gallium-indium-tin alloy dual-phase metal, copper-gallium-indium-tin alloy dual-phase metal, silver-gallium-indium-tin alloy dual-phase metal, gold-gallium-indium-tin alloy dual-phase metal, and neodymium-iron-boron alloy-gallium-indium-tin alloy dual-phase metal.
[0050] As a preferred embodiment of the two-phase metal gel of the third aspect of the present invention, the flexible liquid metal is a gallium-indium alloy, and the mass ratio of gallium to indium in the gallium-indium alloy is 75.50:24.5; or
[0051] The flexible liquid metal is a gallium-indium-tin alloy, and the mass ratio of gallium, indium and tin in the gallium-indium-tin alloy is 68.50:21.50:10.00.
[0052] As a preferred embodiment of the two-phase metal gel of the third aspect of the present invention, the electronic conductivity of the two-phase metal gel is greater than or equal to 2.00×10 6 S / m, toughness greater than or equal to 7MJ·m 3 , the value of Young’s modulus is less than or equal to 7MPa.
[0053] The two-phase metal gel according to the third aspect of the present invention can be prepared by the preparation method provided in the first aspect of the present invention.
[0054] [Flexible Electronics]
[0055] A fourth aspect of the present invention provides a flexible electronic product, comprising the two-phase metal gel described in any embodiment of the second aspect of the present invention or any embodiment of the third aspect of the present invention.
[0056] The novel highly conductive and highly tough flexible electronic product of the present invention comprises a two-phase metal gel composed of a two-phase metal and polyvinyl alcohol; wherein the two-phase metal forms a continuum as the fluid phase of the gel; a three-dimensional continuous polyvinyl alcohol polymer network utilizes interaction to fix the two-phase metal fluid; there is a good interface between the two-phase metals and between the metal and the polymer network, so that the two-phase metal gel and the flexible electronic products containing the two-phase metal gel have better toughness.
[0057] 3. Beneficial effects
[0058] Compared with the prior art, the advantages of the present invention are:
[0059] (1) The two-phase metal gel prepared by the method of the present invention develops a new material system, which realizes the use of two-phase metal as a continuous conductive phase in the gel material for the first time; through the three-layer core-shell structure droplets formed by the two-phase metal and the polymer, a material structure completely different from the existing liquid metal composite material is obtained;
[0060] In addition, the present invention achieves metal-level electronic conductivity by fixing the two-phase metal continuum in a three-dimensional polymer network; and, due to the good compatibility interface between the rigid metal particles, the flexible liquid metal and the polymer network, the stress transfer between the components is enhanced, so that there are three energy dissipation modes inside the material, so that the composite material has excellent toughness, and finally a two-phase metal gel with high electronic conductivity, toughness and flexibility is obtained.
[0061] (2) The different rigid metal particles used in the present invention can form a two-phase metal with the liquid metal, thereby improving the strength and compatibility of the conductive filler, forming a stable interface with the polymer network, and maintaining the stability of the structure and performance of the material after repeated physical deformation or extreme damage;
[0062] (3) A series of two-phase metal gels prepared by the present invention all exhibit high electronic conductivity and high toughness, such as Fig.15 As shown, compared with other high-conductivity composite materials in the prior art, the two-phase metal gel of the present invention stands out in achieving both high conductivity and high toughness; specifically, compared with existing high-conductivity composite materials, the toughness of the two-phase metal gel is at least 6.4 times higher. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 A schematic diagram of a computer tomography image of a two-phase metal gel (liquid metal: copper: polyvinyl alcohol = 12:1:7) in Preparation Example 1 of the present invention;
[0064] Figure 2 A schematic diagram of a polyvinyl alcohol polymer network extracted from a computer tomography image of a two-phase metal gel (liquid metal: copper: polyvinyl alcohol = 12:1:7) in Preparation Example 1 of the present invention;
[0065] Figure 3 A schematic diagram of the structure of a three-layer core-shell structure droplet formed by a copper-gallium-indium alloy two-phase metal and polyvinyl alcohol in Preparation Example 1 of the present invention;
[0066] Figure 4 Schematic diagram of the preparation process of the two-phase metal gel in the preparation example of the present invention;
[0067] Figure 5 It is a statistical schematic diagram of the electronic conductivity of the two-phase metal gel obtained from the copper-gallium-indium alloy two-phase metal and polyvinyl alcohol in Preparation Example 1 of the present invention;
[0068] Figure 6 It is a schematic diagram of the stress-strain curve, toughness and flexibility of the two-phase metal gel obtained by the copper-gallium-indium alloy two-phase metal and polyvinyl alcohol in Preparation Example 1 of the present invention;
[0069] Figure 7 It is a fracture energy curve and fracture energy performance schematic diagram of the two-phase metal gel obtained from the copper-gallium-indium alloy two-phase metal and polyvinyl alcohol in Preparation Example 1 of the present invention;
[0070] Figure 8 The optical photographs of adding copper powder and liquid metal (gallium-indium alloy: copper = 12:1) into a 1M hydrochloric acid solution in Preparation Example 1 of the present invention before and after stirring;
[0071] Fig. 9 :
[0072] (a) is the X-ray diffraction (XRD) pattern of copper powder-liquid metal (gallium-indium alloy: copper = 12:1);
[0073] (b) is the X-ray diffraction (XRD) pattern of iron powder-liquid metal (gallium-indium alloy: iron = 6:1);
[0074] Fig.10 It is a performance schematic diagram of the stress-strain curve, toughness, flexibility and conductivity of the iron-gallium-indium alloy two-phase metal gel in Preparation Example 2 of the present invention;
[0075] Fig.11It is a performance schematic diagram of the stress-strain curve, toughness, flexibility and conductivity of the iron-gallium-indium-tin alloy two-phase metal gel in Preparation Example 3 of the present invention;
[0076] Fig.12 It is a performance schematic diagram of the stress-strain curve, toughness, flexibility and conductivity of the nickel-gallium-indium alloy two-phase metal gel in Preparation Example 4 of the present invention;
[0077] Fig.13 It is a performance schematic diagram of the stress-strain curve, toughness, flexibility and conductivity of the iron-gallium-indium alloy two-phase metal gel in Preparation Example 5 of the present invention;
[0078] Fig.14 It is a performance schematic diagram of the stress-strain curve, toughness, flexibility and conductivity of the nickel-gallium-indium alloy two-phase metal gel in Preparation Example 6 of the present invention;
[0079] Fig.15 It is a schematic diagram showing the performance comparison between the conductivity and toughness of the two-phase metal gel obtained by the copper-gallium-indium alloy two-phase metal and polyvinyl alcohol in Preparation Example 1 of the present invention and other flexible conductive materials;
[0080] Fig.16 Schematic diagram of the performance of the two-phase metal gel prepared with different copper powder particle sizes in Preparation Example 8 of the present invention. DETAILED DESCRIPTION
[0081] The present invention is described in detail below in conjunction with the accompanying drawings and specific preparation examples.
[0082] Preparation Example
[0083] Preparation of materials
[0084] Copper powder (50-100 nm particle size, 1 μm particle size) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., iron powder (1 μm particle size) was purchased from Alfa Aesar (China) Chemical Co., Ltd., nickel powder (1 μm particle size) was purchased from Anhui Zesheng Technology Co., Ltd., neodymium iron boron alloy (1 μm particle size) was purchased from Qinghe County Benyu Metal Materials Co., Ltd., silver powder (1 μm particle size), gold powder (1 μm particle size), copper powder (5-10 μm particle size) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., gallium indium alloy (Ga75.50%) wt ; In 24.50% wt ), Gallium Indium Tin Alloy (Ga 68.50% wt ,;In 21.50% wt ; Sn 10.00% wt ) was purchased from Dongguan Dingyi Metal Co., Ltd., and polyvinyl alcohol particles (1750±50) were purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0085] The copper powders used in Preparation Examples 1-7 are all copper powders with a particle size of 1 μm; the copper powders used in Preparation Example 8 are copper powders with a particle size of 50-100 nm, 1 μm, and 5-10 μm.
[0086] Preparation Example 1
[0087] like Figure 4 As shown, this embodiment discloses a method for preparing a two-phase metal gel, comprising the following steps:
[0088] Preparation of dual phase metal:
[0089] Preparation of copper-gallium-indium alloy dual phase metal:
[0090] Specifically, copper powder particles and gallium-indium alloy (the weight ratio of copper powder particles to gallium-indium alloy is 1:12) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and magnetic stirring is continuously performed at room temperature for 1 hour until the copper powder particles are completely infiltrated in the gallium-indium alloy, and the copper-gallium-indium alloy two-phase metal is obtained after washing away the hydrochloric acid;
[0091] Preparation of silver-gallium-indium alloy dual phase metal:
[0092] Specifically, silver powder particles and gallium-indium alloy (the weight ratio of silver powder particles to gallium-indium alloy is 1:12) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and magnetic stirring is continuously performed at room temperature for 1 hour until the silver powder particles are completely infiltrated into the gallium-indium alloy, and the hydrochloric acid is washed off to obtain a silver-gallium-indium alloy two-phase metal;
[0093] Preparation of gold-gallium-indium alloy dual phase metal:
[0094] Specifically, gold powder particles and gallium-indium alloy (the weight ratio of gold powder particles to gallium-indium alloy is 1:12) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and magnetic stirring is continuously performed at room temperature for 1 hour until the gold powder particles are completely infiltrated into the gallium-indium alloy, and the hydrochloric acid is washed off to obtain a gold-gallium-indium alloy two-phase metal;
[0095] Preparation of copper-gallium-indium-tin alloy dual phase metal:
[0096] Specifically, copper powder particles and gallium indium tin alloy (the weight ratio of copper powder particles to gallium indium tin alloy is 1:12) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and magnetic stirring is continuously performed at room temperature for 1 hour until the copper powder particles are completely infiltrated in the gallium indium tin alloy, and the copper-gallium indium tin alloy two-phase metal is obtained after washing away the hydrochloric acid;
[0097] Preparation of silver-gallium-indium-tin alloy dual phase metal:
[0098] Specifically, silver powder particles and gallium indium tin alloy (the weight ratio of silver powder particles to gallium indium tin alloy is 1:12) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and magnetic stirring is continuously performed at room temperature for 1 hour until the silver powder particles are completely infiltrated in the gallium indium tin alloy, and the hydrochloric acid is washed off to obtain a silver-gallium indium tin alloy two-phase metal;
[0099] Preparation of Au-GaInSn alloy dual phase metal:
[0100] Specifically, gold powder particles and gallium indium tin alloy (the weight ratio of gold powder particles to gallium indium tin alloy is 1:12) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and magnetic stirring is continuously performed at room temperature for 1 hour until the gold powder particles are completely infiltrated in the gallium indium tin alloy, and the hydrochloric acid is washed off to obtain a gold-gallium indium tin alloy two-phase metal;
[0101] Preparation of Iron-Gallium-Indium alloy dual phase metal:
[0102] Specifically, iron powder particles and gallium-indium alloy (the weight ratio of iron powder particles to gallium-indium alloy is 1:6) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and stirring is continued at room temperature for 30 minutes until the iron powder particles are completely infiltrated into the gallium-indium alloy, and the hydrochloric acid is washed off to obtain an iron-gallium-indium alloy two-phase metal;
[0103] Preparation of nickel-gallium-indium alloy dual phase metal:
[0104] Specifically, nickel powder particles and gallium-indium alloy (the weight ratio of nickel powder particles to gallium-indium alloy is 1:6) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and stirring is continued at room temperature for 30 minutes until the nickel powder particles are completely infiltrated into the gallium-indium alloy, and the hydrochloric acid is washed off to obtain a nickel-gallium-indium alloy two-phase metal;
[0105] Preparation of NdFeB alloy-GaIn alloy dual phase metal:
[0106] Specifically, NdFeB alloy particles and GaIn alloy (the weight ratio of NdFeB alloy particles to GaIn alloy is 1:6) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and stirring is continued at room temperature for 30 minutes until the NdFeB alloy particles are completely infiltrated in the GaIn alloy, and the hydrochloric acid is washed off to obtain a NdFeB alloy-GaIn alloy two-phase metal;
[0107] Preparation of Iron-Gallium-Indium-Tin Alloy Dual Phase Metal:
[0108] Specifically, iron powder particles and gallium indium tin alloy (the weight ratio of iron powder particles to gallium indium tin alloy is 1:6) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and stirring is continued at room temperature for 30 minutes until the iron powder particles are completely infiltrated in the gallium indium tin alloy, and the hydrochloric acid is washed off to obtain an iron-gallium indium tin alloy two-phase metal;
[0109] Preparation of nickel-gallium-indium-tin alloy dual phase metal:
[0110] Specifically, nickel powder particles and gallium indium tin alloy (the weight ratio of nickel powder particles to gallium indium tin alloy is 1:6) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and stirring is continued at room temperature for 30 minutes until the nickel powder particles are completely infiltrated in the gallium indium tin alloy, and the hydrochloric acid is washed off to obtain a nickel-gallium indium tin alloy two-phase metal;
[0111] Preparation of NdFeB alloy-GaInSn alloy dual phase metal:
[0112] Specifically, NdFeB alloy particles and GaInSn alloy (the weight ratio of NdFeB alloy particles to GaInSn alloy is 1:6) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and stirring is continued at room temperature for 30 minutes until the NdFeB alloy particles are infiltrated into the GaInSn alloy, and the hydrochloric acid is washed off to obtain a NdFeB alloy-GaInSn alloy two-phase metal;
[0113] Prepare polyvinyl alcohol solution:
[0114] Specifically, the steps of preparing the polyvinyl alcohol solution are as follows: dissolving 10 wt % of polyvinyl alcohol particles in deionized water, and continuously stirring with magnetic force at a temperature of 95° C. for 1 hour until dissolved, to obtain the polyvinyl alcohol solution.
[0115] Preparation of two-phase metal-polyvinyl alcohol mixed solution:
[0116] The copper-gallium-indium alloy two-phase metal, the silver-gallium-indium alloy two-phase metal, the gold-gallium-indium alloy two-phase metal, the copper-gallium-indium-tin alloy two-phase metal, the silver-gallium-indium-tin alloy two-phase metal, and the gold-gallium-indium-tin alloy two-phase metal are respectively mixed with the polyvinyl alcohol solution at a weight ratio of 13:7;
[0117] The iron-gallium-indium alloy two-phase metal, the nickel-gallium-indium alloy two-phase metal, the neodymium-iron-boron alloy-gallium-indium alloy two-phase metal, the iron-gallium-indium-tin alloy two-phase metal, the nickel-gallium-indium-tin alloy two-phase metal, and the neodymium-iron-boron alloy-gallium-indium-tin alloy two-phase metal are respectively mixed with the polyvinyl alcohol solution at a weight ratio of 7:7;
[0118] Then, each mixed solution was stirred and sheared at room temperature with a handheld homogenizer at a speed of 15000 rpm for 5 min to obtain uniformly dispersed two-phase metal-polyvinyl alcohol mixed solutions of twelve systems;
[0119] dry:
[0120] The uniformly dispersed two-phase metal-polyvinyl alcohol mixed solution is heated to remove the good solvent.
[0121] Specifically, twelve systems of two-phase metal-polyvinyl alcohol mixed solutions were added into polytetrafluoroethylene watch glasses respectively, and then placed in an environment of 60° C. to remove the good solvent, thereby obtaining twelve two-phase metal gels.
[0122] Table 1. Weight ratio of liquid metal to rigid metal and polyvinyl alcohol solution, Young's modulus, electronic conductivity and toughness of twelve two-phase metal gels
[0123]
[0124]
[0125] As shown in Table 1, according to the above steps, two-phase metal gels can be successfully prepared based on different two-phase metals (iron-gallium-indium alloy two-phase metal, nickel-gallium-indium alloy two-phase metal, copper-gallium-indium alloy two-phase metal, silver-gallium-indium alloy two-phase metal, gold-gallium-indium alloy two-phase metal, neodymium-iron-boron alloy-gallium-indium alloy two-phase metal, iron-gallium-indium-tin alloy two-phase metal, nickel-gallium-indium-tin alloy two-phase metal, copper-gallium-indium-tin alloy two-phase metal, silver-gallium-indium-tin alloy two-phase metal, gold-gallium-indium-tin alloy two-phase metal, neodymium-iron-boron alloy-gallium-indium-tin alloy two-phase metal) and polyvinyl alcohol. And the prepared two-phase metal gels all have excellent electronic conductivity, high toughness and appropriate flexibility.
[0126] Specifically, the electronic conductivity of the prepared two-phase metal gel material is greater than 2.00×10 6 S / m, toughness is higher than 7MJ·m 3 , and the values of Young’s modulus are all lower than 7MPa, achieving a balance between high electronic conductivity, high toughness and flexibility.
[0127] like Figure 1 , which is a schematic diagram of a computer tomography image of the two-phase metal gel (liquid metal: copper: polyvinyl alcohol = 12:1:7) in Preparation Example 1 of the present invention;
[0128] Among them, the two-phase metal as the fluid phase in the two-phase metal gel is an interconnected continuum, in which the liquid metal occupies 75.54% of the volume fraction and the rigid metal particles occupy 2.09% of the volume fraction; as a three-dimensional continuous polymer network, polyvinyl alcohol occupies 22.37% of the volume fraction.
[0129] like Figure 2 As shown, Figure 1 Schematic diagram of the polyvinyl alcohol polymer network extracted from the computed tomography image.
[0130] like Figure 3 , which is a schematic diagram of the structure of a three-layer core-shell structure droplet formed by a copper-gallium-indium alloy two-phase metal and polyvinyl alcohol in Preparation Example 1.
[0131] like Figure 5 The figure shows the statistical diagram of the electronic conductivity of the copper-gallium-indium alloy two-phase metal gel. The conductivity of the copper-gallium-indium alloy two-phase metal gel has good repeatability and exhibits stable electromechanical coupling performance. The maximum conductivity can reach 2.52×10 6 S / m.
[0132] like Figure 6 The stress-strain curve of the copper-gallium-indium alloy two-phase metal gel and the corresponding performance diagram of toughness and flexibility are shown in Figure 1. The average toughness of the copper-gallium-indium alloy two-phase metal gel is 14.40MJ / m 3 , the average Young's modulus is 6.80MPa.
[0133] like Figure 7 The fracture energy curve of copper-gallium-indium alloy two-phase metal gel and the corresponding fracture energy performance diagram are shown. The average fracture energy of copper-gallium-indium alloy two-phase metal gel is 20.41 kJ / m 2 .
[0134] like Figure 8 As shown in FIG. 1 , copper powder and liquid metal (gallium-indium alloy: copper = 12:1) are added to a 1M hydrochloric acid solution, and optical photos are taken before and after stirring. From the optical picture, it can be seen that the copper powder has been completely immersed in the liquid metal.
[0135] like Fig. 9 (a) shows the X-ray diffraction (XRD) pattern of copper powder-liquid metal (gallium-indium alloy: copper = 12:1);
[0136] like Fig. 9 (b) shows the X-ray diffraction (XRD) pattern of iron powder-liquid metal (gallium-indium alloy: iron = 6:1);
[0137] Depend on Fig. 9 It can be seen that copper powder and liquid metal form an intermetallic compound CuGa2, while iron powder and liquid metal do not form an intermetallic compound. This is the reason why the toughness of copper two-phase metal gel is significantly higher than that of other rigid metal particle two-phase metal gels.
[0138] like Fig.15 As shown, the electrical conductivity and toughness of copper-gallium-indium alloy two-phase metal gel far exceed the performance of other flexible conductive materials.
[0139] Preparation Example 2
[0140] Preparation of Iron-Gallium-Indium alloy dual phase metal:
[0141] Specifically, iron powder particles and gallium-indium alloy (the weight ratio of iron powder particles to gallium-indium alloy is 1:7) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is 5:1, and stirring is continued at room temperature for 30 minutes until the iron powder particles are completely infiltrated into the gallium-indium alloy, and the hydrochloric acid is washed off to obtain an iron-gallium-indium alloy two-phase metal;
[0142] Prepare polyvinyl alcohol solution:
[0143] Specifically, the steps of preparing the polyvinyl alcohol solution are as follows: dissolving 10 wt % of polyvinyl alcohol particles in deionized water, and continuously stirring with magnetic force at a temperature of 95° C. for 1 hour until dissolved, to obtain the polyvinyl alcohol solution.
[0144] Preparation of two-phase metal-polyvinyl alcohol mixed solution:
[0145] The above two-phase metal and polyvinyl alcohol solution were mixed in a weight ratio of 2:1, and then stirred and sheared at a speed of 15000 rpm for 5 minutes using a handheld homogenizer at room temperature to obtain an iron-gallium-indium alloy two-phase metal-polyvinyl alcohol mixed solution;
[0146] dry:
[0147] The uniformly dispersed mixed solution is heated to remove the good solvent.
[0148] Specifically, the obtained iron-gallium-indium alloy two-phase metal-polyvinyl alcohol mixed solution is added into a polytetrafluoroethylene watch glass, which is then placed in an environment of 60° C. to remove the good solvent, thereby obtaining the iron-gallium-indium alloy two-phase metal gel.
[0149] like Fig.10 As shown in Figure 2, the electronic conductivity of the Fe-GaIn alloy two-phase metal gel is 2.10×10 6 S / m, toughness is 8.48MJ / m 3 , Young’s modulus is 5.58MPa.
[0150] Preparation Example 3
[0151] Preparation of Iron-Gallium-Indium-Tin Alloy Dual Phase Metal:
[0152] Specifically, iron powder particles and gallium indium tin alloy (the weight ratio of iron powder particles to gallium indium tin alloy is 1:7) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is 5:1, and stirring is continued at room temperature for 30 minutes until the iron powder particles are completely infiltrated in the gallium indium tin alloy, and the hydrochloric acid is washed off to obtain an iron-gallium indium tin alloy two-phase metal;
[0153] Prepare polyvinyl alcohol solution:
[0154] Specifically, the steps of preparing the polyvinyl alcohol solution are as follows: dissolving 10 wt % of polyvinyl alcohol particles in deionized water, and continuously stirring with magnetic force at a temperature of 95° C. for 1 hour until dissolved, to obtain the polyvinyl alcohol solution.
[0155] Preparation of two-phase metal-polyvinyl alcohol mixed solution:
[0156] The above two-phase metal and polyvinyl alcohol solution were mixed in a weight ratio of 3:2, and then stirred and sheared at a speed of 15000 rpm for 5 minutes using a handheld homogenizer at room temperature to obtain an iron-gallium indium tin alloy two-phase metal-polyvinyl alcohol mixed solution;
[0157] dry:
[0158] The uniformly dispersed two-phase metal-polyvinyl alcohol mixed solution is heated to remove the good solvent.
[0159] Specifically, the obtained iron-gallium indium tin alloy two-phase metal-polyvinyl alcohol mixed solution is added into a polytetrafluoroethylene watch glass, which is then placed in an environment of 60° C. to remove the good solvent, thereby obtaining the iron-gallium indium tin alloy two-phase metal gel.
[0160] like Fig.11 As shown in Figure 2, the electronic conductivity of the Fe-GaInSn alloy two-phase metal gel is 2.22×10 6 S / m, toughness is 8.79MJ / m 3 , Young’s modulus is 3.84MPa.
[0161] Preparation Example 4
[0162] Preparation of nickel-gallium-indium alloy dual phase metal:
[0163] Specifically, nickel powder particles and gallium-indium alloy (the weight ratio of nickel powder particles to gallium-indium alloy is 1:6) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is 5:1, and stirring is continued at room temperature for 30 minutes until the nickel powder particles are completely infiltrated into the gallium-indium alloy, and the hydrochloric acid is washed off to obtain a nickel-gallium-indium alloy two-phase metal;
[0164] Prepare polyvinyl alcohol solution:
[0165] Specifically, the steps of preparing the polyvinyl alcohol solution are as follows: dissolving 10 wt % of polyvinyl alcohol particles in deionized water, and continuously stirring with magnetic force at a temperature of 95° C. for 1 hour until dissolved, to obtain the polyvinyl alcohol solution.
[0166] Preparation of two-phase metal-polyvinyl alcohol mixed solution:
[0167] The above two-phase metal and polyvinyl alcohol solution were mixed in a weight ratio of 3:2, and then stirred and sheared at a speed of 15000 rpm for 5 minutes using a handheld homogenizer at room temperature to obtain a nickel-gallium-indium alloy two-phase metal-polyvinyl alcohol mixed solution;
[0168] dry:
[0169] The uniformly dispersed two-phase metal-polyvinyl alcohol mixed solution is heated to remove the good solvent.
[0170] Specifically, the obtained nickel-gallium-indium alloy two-phase metal-polyvinyl alcohol mixed solution was added into a polytetrafluoroethylene watch dish, which was then placed in an environment of 60° C. to remove the good solvent, thereby obtaining the nickel-gallium-indium alloy two-phase metal gel.
[0171] like Fig.12 As shown in Figure 2, the electronic conductivity of the Ni-Ga-In alloy two-phase metal gel is 2.15×10 6 S / m, toughness is 14.6MJ / m 3 , Young’s modulus is 4.5MPa.
[0172] Preparation Example 5
[0173] Preparation of Iron-Gallium-Indium alloy dual phase metal:
[0174] Specifically, iron powder particles and gallium-indium alloy (the weight ratio of iron powder particles to gallium-indium alloy is 1:12) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is 5:1, and stirring is continued at room temperature for 30 minutes until the iron powder particles are completely infiltrated into the gallium-indium alloy, and the hydrochloric acid is washed off to obtain an iron-gallium-indium alloy two-phase metal;
[0175] Prepare polyvinyl alcohol solution:
[0176] Specifically, the steps of preparing the polyvinyl alcohol solution are as follows: dissolving 10 wt % of polyvinyl alcohol particles in deionized water, and continuously stirring with magnetic force at a temperature of 95° C. for 1 hour until dissolved, to obtain the polyvinyl alcohol solution.
[0177] Preparation of two-phase metal-polyvinyl alcohol mixed solution:
[0178] The above two-phase metal and polyvinyl alcohol solution were mixed in a weight ratio of 3:2, and then stirred and sheared at a speed of 15000 rpm for 5 minutes using a handheld homogenizer at room temperature to obtain an iron-gallium-indium alloy two-phase metal-polyvinyl alcohol mixed solution;
[0179] dry:
[0180] The uniformly dispersed two-phase metal-polyvinyl alcohol mixed solution is heated to remove the good solvent.
[0181] Specifically, the obtained iron-gallium-indium alloy two-phase metal-polyvinyl alcohol mixed solution is added into a polytetrafluoroethylene watch glass, which is then placed in an environment of 60° C. to remove the good solvent, thereby obtaining the iron-gallium-indium alloy two-phase metal gel.
[0182] like Fig.13 As shown in Figure 2, the electronic conductivity of the Fe-GaIn alloy two-phase metal gel is 2.07×10 6 S / m, toughness is 7.99MJ / m 3 , Young’s modulus is 4.2MPa.
[0183] Preparation Example 6
[0184] Preparation of nickel-gallium-indium alloy dual phase metal:
[0185] Specifically, nickel powder particles and gallium-indium alloy (the weight ratio of nickel powder particles to gallium-indium alloy is 1:11) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is 5:1, and stirring is continued at room temperature for 30 minutes until the nickel powder particles are completely infiltrated into the gallium-indium alloy, and the hydrochloric acid is washed off to obtain a nickel-gallium-indium alloy two-phase metal;
[0186] Prepare polyvinyl alcohol solution:
[0187] Specifically, the steps of preparing the polyvinyl alcohol solution are as follows: dissolving 10 wt % of polyvinyl alcohol particles in deionized water, and continuously stirring with magnetic force at a temperature of 95° C. for 1 hour until dissolved, to obtain the polyvinyl alcohol solution.
[0188] Preparation of two-phase metal-polyvinyl alcohol mixed solution:
[0189] The above two-phase metal and polyvinyl alcohol solution were mixed in a weight ratio of 3:2, and then stirred and sheared at a speed of 15000 rpm for 5 minutes using a handheld homogenizer at room temperature to obtain a nickel-gallium-indium alloy two-phase metal-polyvinyl alcohol mixed solution;
[0190] dry:
[0191] The uniformly dispersed two-phase metal-polyvinyl alcohol mixed solution is heated to remove the good solvent.
[0192] Specifically, the obtained nickel-gallium-indium alloy two-phase metal-polyvinyl alcohol mixed solution was added into a polytetrafluoroethylene watch dish, which was then placed in an environment of 60° C. to remove the good solvent, thereby obtaining the nickel-gallium-indium alloy two-phase metal gel.
[0193] like Fig.14 As shown in Figure 2, the electronic conductivity of the Ni-Ga-In alloy two-phase metal gel is 2.10×10 6 S / m, toughness is 9.83MJ / m 3 , Young’s modulus is 4.9MPa.
[0194] Preparation Example 7
[0195] Preparation of dual phase metal:
[0196] Preparation of copper-gallium-indium alloy dual phase metal;
[0197] Specifically, copper powder particles and gallium-indium alloy were added to a 4M sodium hydroxide solution at a weight ratio of 1:12, and magnetic stirring was continued at room temperature for 1 hour until the copper powder particles were infiltrated into the gallium-indium alloy, and the sodium hydroxide was washed off to obtain a copper-gallium-indium alloy two-phase metal;
[0198] Preparation of silver-gallium-indium alloy dual-phase metal;
[0199] Specifically, silver powder particles and gallium-indium alloy were added to a 4M sodium hydroxide solution at a weight ratio of 1:12, and magnetic stirring was continued at room temperature for 1 hour until the silver powder particles were infiltrated into the gallium-indium alloy, and the sodium hydroxide was washed off to obtain a silver-gallium-indium alloy two-phase metal;
[0200] Preparation of gold-gallium-indium alloy dual phase metal;
[0201] Specifically, gold powder particles and gallium-indium alloy were added to a 4M sodium hydroxide solution at a weight ratio of 1:12, and magnetic stirring was continued at room temperature for 1 hour until the gold powder particles were infiltrated into the gallium-indium alloy, and the sodium hydroxide was washed off to obtain a gold-gallium-indium alloy two-phase metal;
[0202] Preparation of copper-gallium-indium-tin alloy dual phase metal;
[0203] Specifically, copper powder particles and gallium indium tin alloy are added to a 4M sodium hydroxide solution at a weight ratio of 1:12, and magnetic stirring is continuously performed at room temperature for 1 hour until the copper powder particles are infiltrated into the gallium indium tin alloy, and the sodium hydroxide is washed off to obtain a copper-gallium indium tin alloy two-phase metal;
[0204] Preparation of silver-gallium-indium-tin alloy dual phase metal;
[0205] Specifically, silver powder particles and gallium indium tin alloy are added to a 4M sodium hydroxide solution at a weight ratio of 1:12, and magnetic stirring is continuously performed at room temperature for 1 hour until the silver powder particles are infiltrated into the gallium indium tin alloy, and the sodium hydroxide is washed off to obtain a silver-gallium indium tin alloy two-phase metal;
[0206] Preparation of gold-gallium-indium-tin alloy dual phase metal;
[0207] Specifically, gold powder particles and gallium indium tin alloy were added to a 4M sodium hydroxide solution at a weight ratio of 1:12, and magnetic stirring was continued at room temperature for 1 hour until the gold powder particles were infiltrated into the gallium indium tin alloy, and the sodium hydroxide was washed off to obtain a gold-gallium indium tin alloy two-phase metal;
[0208] Preparation of iron-gallium-indium alloy dual phase metal;
[0209] Specifically, iron powder particles and gallium-indium alloy were added to a 4M sodium hydroxide solution at a weight ratio of 1:6, and the mixture was stirred continuously at room temperature for 0.5 hours until the iron powder particles were soaked in the gallium-indium alloy. After washing the sodium hydroxide, an iron-gallium-indium alloy two-phase metal was obtained.
[0210] Preparation of nickel-gallium-indium alloy dual phase metal;
[0211] Specifically, nickel powder particles and gallium-indium alloy were added to a 4M sodium hydroxide solution at a weight ratio of 1:6, and the mixture was stirred continuously at room temperature for 0.5 hours until the nickel powder particles were soaked in the gallium-indium alloy. After washing the sodium hydroxide, a nickel-gallium-indium alloy two-phase metal was obtained.
[0212] Preparation of NdFeB alloy-GaIn alloy dual phase metal;
[0213] Specifically, NdFeB alloy particles and GaIn alloy were added to a 4M sodium hydroxide solution at a weight ratio of 1:6, and the mixture was stirred continuously at room temperature for 0.5 hours until the NdFeB alloy particles were infiltrated into the GaIn alloy, and the sodium hydroxide was washed off to obtain a NdFeB alloy-GaIn alloy two-phase metal;
[0214] Preparation of iron-gallium-indium-tin alloy dual phase metal;
[0215] Specifically, iron powder particles and gallium indium tin alloy are added to a 4M sodium hydroxide solution at a weight ratio of 1:6, and stirred continuously at room temperature for 0.5 hours until the copper powder particles are infiltrated into the gallium indium tin alloy, and the sodium hydroxide is washed off to obtain an iron-gallium indium tin alloy two-phase metal;
[0216] Preparation of nickel-gallium-indium-tin alloy dual phase metal;
[0217] Specifically, nickel powder particles and gallium indium tin alloy are added to 4M sodium hydroxide solution at a weight ratio of 1:6, and stirred continuously at room temperature for 0.5 hours until the nickel powder particles are infiltrated into the gallium indium tin alloy, and the sodium hydroxide is washed off to obtain a nickel-gallium indium tin alloy two-phase metal;
[0218] Preparation of NdFeB alloy-GaInSn alloy dual phase metal;
[0219] Specifically, NdFeB alloy particles and GaInSn alloy are added to a 4M sodium hydroxide solution at a weight ratio of 1:6, and stirred continuously at room temperature for 0.5 hours until the NdFeB alloy particles are infiltrated into the GaInSn alloy, and the sodium hydroxide is washed off to obtain a NdFeB alloy-GaInSn alloy two-phase metal;
[0220] Prepare polyvinyl alcohol solution:
[0221] Specifically, the steps of preparing the polyvinyl alcohol solution are as follows: dissolving 10 wt % of polyvinyl alcohol particles in deionized water, and continuously stirring with magnetic force at a temperature of 95° C. for 1 hour until dissolved, to obtain the polyvinyl alcohol solution.
[0222] Preparation of two-phase metal-polyvinyl alcohol mixed solution:
[0223] The copper-gallium-indium alloy two-phase metal, the silver-gallium-indium alloy two-phase metal, the gold-gallium-indium alloy two-phase metal, the copper-gallium-indium-tin alloy two-phase metal, the silver-gallium-indium-tin alloy two-phase metal, and the gold-gallium-indium-tin alloy two-phase metal are respectively mixed with the polyvinyl alcohol solution at a weight ratio of 13:7;
[0224] The iron-gallium-indium alloy two-phase metal, the nickel-gallium-indium alloy two-phase metal, the neodymium-iron-boron alloy-gallium-indium alloy two-phase metal, the iron-gallium-indium-tin alloy two-phase metal, the nickel-gallium-indium-tin alloy two-phase metal, and the neodymium-iron-boron alloy-gallium-indium-tin alloy two-phase metal are respectively mixed with the polyvinyl alcohol solution at a weight ratio of 7:7;
[0225] Then, the mixture was stirred and sheared at 15000 rpm for 5 min at room temperature using a handheld homogenizer to obtain twelve systems of two-phase metal-polyvinyl alcohol mixed solutions;
[0226] dry:
[0227] The uniformly dispersed two-phase metal-polyvinyl alcohol mixed solution is heated to remove the good solvent.
[0228] Specifically, twelve systems of two-phase metal-polyvinyl alcohol mixed solutions were added into polytetrafluoroethylene watch glasses respectively, and then placed in an environment of 60° C. to remove the good solvent, thereby obtaining twelve two-phase metal gels.
[0229] After testing, the electronic conductivity, toughness and Young's modulus of the two-phase metal gel obtained in Preparation Example 7 under alkaline conditions are comparable to those of the corresponding two-phase metal gel obtained in Preparation Example 1 under acidic conditions.
[0230] Preparation Example 8
[0231] Preparation of copper-gallium-indium alloy dual phase metal:
[0232] Specifically, copper powder particles with a particle size of 50-100 nm and gallium-indium alloy (the weight ratio of copper powder particles to gallium-indium alloy is 1:12) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and magnetic stirring is continuously performed at room temperature for 1 hour until the copper powder particles are completely infiltrated into the gallium-indium alloy, and after washing off the hydrochloric acid, a copper-gallium-indium alloy two-phase metal with a particle size of 50-100 nm is obtained;
[0233] Specifically, copper powder particles with a particle size of 1 μm and gallium-indium alloy (the weight ratio of copper powder particles to gallium-indium alloy is 1:12) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and magnetic stirring is continuously performed at room temperature for 1 hour until the copper powder particles are completely infiltrated into the gallium-indium alloy, and the hydrochloric acid is washed off to obtain a copper-gallium-indium alloy two-phase metal with a particle size of 1 μm;
[0234] Specifically, copper powder particles with a particle size of 5-10 μm and gallium-indium alloy (the weight ratio of copper powder particles to gallium-indium alloy is 1:12) are added to a 1M hydrochloric acid solution, the volume ratio of hydrochloric acid to metal is about 5:1, and magnetic stirring is continuously performed at room temperature for 1 hour until the copper powder particles are completely infiltrated into the gallium-indium alloy, and after washing away the hydrochloric acid, a copper-gallium-indium alloy two-phase metal with a particle size of 5-10 μm is obtained;
[0235] Prepare polyvinyl alcohol solution:
[0236] Specifically, the steps of preparing the polyvinyl alcohol solution are as follows: dissolving 10 wt % of polyvinyl alcohol particles in deionized water, and continuously stirring with magnetic force at a temperature of 95° C. for 1 hour until dissolved, to obtain the polyvinyl alcohol solution.
[0237] Preparation of two-phase metal-polyvinyl alcohol mixed solution:
[0238] The copper-gallium-indium alloy two-phase metals of the three particle sizes were mixed with the polyvinyl alcohol solution at a weight ratio of 13:7, and then the mixed solutions were stirred and sheared at a speed of 15000 rpm for 5 minutes using a handheld homogenizer at room temperature to obtain uniformly dispersed copper-gallium-indium alloy two-phase metal-polyvinyl alcohol mixed solutions of the three particle sizes;
[0239] dry:
[0240] The uniformly dispersed two-phase metal-polyvinyl alcohol mixed solution is heated to remove the good solvent.
[0241] Specifically, the obtained copper-gallium-indium alloy two-phase metal-polyvinyl alcohol mixed solutions of three particle sizes were added into polytetrafluoroethylene watch glasses respectively, and then placed in an environment of 60° C. to remove the good solvent, thereby obtaining copper-gallium-indium alloy two-phase metal gels of three particle sizes.
[0242] like Fig.16 As shown, the copper-gallium-indium alloy two-phase metal gels of three particle sizes all have excellent electronic conductivity and high toughness.
[0243] Specifically, the electronic conductivity of the prepared two-phase metal gel material is greater than 2.00×10 6 S / m, toughness is higher than 12MJ·m 3 , achieving both high electronic conductivity and high toughness.
[0244] In summary, the two-phase metals are interconnected in the entire material to form a continuous phase, which provides a good electronic path for the two-phase metal gel. The two-phase metal gel has an electronic conductivity close to the metal level, and the minimum can reach 2.00×10 6 The polyvinyl alcohol polymer network presents a continuous three-dimensional porous structure, which provides good mechanical support for the two-phase metal gel and has excellent toughness, reaching at least 7MJ / m 3 , and also has good flexibility, with a Young's modulus of less than 7MPa. There is a hydrogen bond interaction between the polyvinyl alcohol polymer network and the two-phase metal, which fixes the two-phase metal in the nano-scale dispersed polyvinyl alcohol polymer network and ensures that the two-phase metal does not leak, forming a stable interface between the components, so that the material has good electronic conductivity and flexibility, as well as excellent toughness.
[0245] The above schematically describes the invention and its implementation methods, which is not restrictive. Without departing from the spirit or basic features of the invention, the invention can be implemented in other specific forms. What is shown in the accompanying drawings is only one of the implementation methods of the invention. The actual structure is not limited to this, and any figure mark in the claims should not limit the claims involved. Therefore, if a person of ordinary skill in the art is inspired by it, without departing from the purpose of the invention, a structural method and an embodiment similar to the technical solution are designed without creativity, which should all fall within the scope of protection of this patent. In addition, the word "including" does not exclude other elements or steps, and the word "one" before the element does not exclude the inclusion of "multiple" elements. The multiple elements stated in the product claim can also be implemented by one element through software or hardware. The words first, second, etc. are used to indicate names, and do not indicate any specific order.
Claims
1. A method for preparing a two-phase metal gel, characterized in that The following steps are involved: Preparation of dual-phase metal: rigid metal particles and flexible liquid metal are mixed in an acidic solution or an alkaline solution, and separated after continuous stirring to obtain dual-phase metal; Preparing a polyvinyl alcohol solution: dissolving polyvinyl alcohol in a good solvent to obtain a polyvinyl alcohol solution; Preparing a two-phase metal-polyvinyl alcohol mixed solution: mixing and dispersing the two-phase metal with the polyvinyl alcohol solution to obtain a two-phase metal-polyvinyl alcohol mixed solution; Drying: drying the two-phase metal-polyvinyl alcohol mixed solution to obtain a two-phase metal gel.
2. The method for preparing the two-phase metal gel according to claim 1, characterized in that: The rigid metal particles are selected from one or more of iron, nickel, copper, silver, gold or neodymium iron boron alloy; The flexible liquid metal is selected from one or both of gallium-indium alloy and gallium-indium-tin alloy.
3. The method for preparing the two-phase metal gel according to claim 2, characterized in that: The rigid metal particles are copper.
4. The method for preparing the two-phase metal gel according to claim 2, characterized in that: The two-phase metal is selected from one or more of iron-gallium-indium alloy two-phase metal, nickel-gallium-indium alloy two-phase metal, copper-gallium-indium alloy two-phase metal, silver-gallium-indium alloy two-phase metal, gold-gallium-indium alloy two-phase metal, neodymium-iron-boron alloy-gallium-indium alloy two-phase metal, iron-gallium-indium-tin alloy two-phase metal, nickel-gallium-indium-tin alloy two-phase metal, copper-gallium-indium-tin alloy two-phase metal, silver-gallium-indium-tin alloy two-phase metal, gold-gallium-indium-tin alloy two-phase metal, and neodymium-iron-boron alloy-gallium-indium-tin alloy two-phase metal.
5. The method for preparing the two-phase metal gel according to claim 4, characterized in that: In the two-phase metal, the rigid metal particles have a size of 50 nm to 10 μm; In the two-phase metal, the mass ratio of rigid metal particles to flexible liquid metal is 1:(6-20); The mass ratio of the two-phase metal to the polyvinyl alcohol solution is (3-7):
3.
6. The method for preparing the two-phase metal gel according to claim 4, characterized in that: The flexible liquid metal is a gallium-indium alloy, and the mass ratio of gallium to indium in the gallium-indium alloy is 75.50:24.5; or The flexible liquid metal is a gallium-indium-tin alloy, and the mass ratio of gallium, indium and tin in the gallium-indium-tin alloy is 68.50:21.50:10.
00.
7. The method for preparing the two-phase metal gel according to claim 4, characterized in that: In the step of preparing the dual-phase metal, the concentration of the acidic solution or alkaline solution is 1 to 4 M; In the step of preparing the polyvinyl alcohol solution, the good solvent is selected from one or two of deionized water and dimethyl sulfoxide; The concentration of the polyvinyl alcohol solution is 8wt%-12wt%; In the step of preparing the two-phase metal-polyvinyl alcohol mixed solution, the stirring speed of the mixed dispersion is 8000 rpm to 15000 rpm, and the stirring time is 5 to 15 minutes.
8. A two-phase metal gel, characterized in that: The invention comprises a dual-phase metal and polyvinyl alcohol, wherein the dual-phase metal is dispersed in the polyvinyl alcohol; The two-phase metal comprises rigid metal particles and flexible liquid metal; In the two-phase metal, the rigid metal particles have a size of 50 nm to 10 μm; In the two-phase metal, the mass ratio of rigid metal particles to flexible liquid metal is 1:(6-20); The mass ratio of the two-phase metal to polyvinyl alcohol is (30-70):
3.
9. The two-phase metal gel according to claim 8, characterized in that: The electronic conductivity of the two-phase metal gel is greater than or equal to 2.00×10 6 S / m, toughness greater than or equal to 7MJ·m 3 , the value of Young’s modulus is less than or equal to 7MPa.
10. A flexible electronic product comprising the two-phase metal gel according to claim 8 or 9.
Citation Information
Patent Citations
Method for doping micro nanoparticles into liquid metal and application of liquid metal-micro nanoparticle mixture
CN108085519A
Liquid metal flexible patch for CT positioning and preparation method of liquid metal flexible patch
CN113491584A
Bimodal liquid metal compound for CT and magnetic resonance imaging positioning
CN113827741A
Liquid metal functional composite film and preparation method thereof
CN114525002A
Liquid metal hydrogel as well as preparation method and application thereof
CN116462861A